Paediatric Pelvic Tumours; Presentation, Diagnosis and Challenges of Treatment in a Low Resource Setting - Okoro Philemon E; Eke Gracia (Asian Journal of Clinical Pediatrics and Neonatology, 2019)
Background: Paediatric pelvic solid tumours present peculiar challenge in clinical diagnosis due to their inherently obscure anatomic location, and the varied, often vague symptoms. Difficult surgical access and presence of important surrounding pelvic structures make their surgical treatment particularly challenging.Aim: To report our experience with paediatric pelvic solid tumours and to highlight the presentation pattern and challenges of diagnosis and treatment in our setting. Subjects and Methods: This is a five year retrospective study of pelvic solid tumours in children seen in our centre between December 2013 and November 2018. Data retrieved were demographics, presenting symptoms and duration, previous treatments, findings on examination, laboratory investigations, treatment given in our centre, histology of tumours and duration of follow up, outcome. Analysis was done on Microsoft Excel spread sheet Windows 2007. Results: Twenty three cases comprising 7 males and 16 females were included in this study. The age range was 1 to 14 years with a median at 6.5 years. Ten(43.5%) of these cases were benign, and 13(56.5%) were malignant. The teratomas comprised 9 benign cystic mature teratomas and 6 malignant teratomas. There were 4 mortalities and one recurrence. Conclusion: The anatomic location and vague early symptoms of pelvic tumours make early diagnosis difficult in our setting. High morbidity and mortality is the direct consequence. In a resource poor setting as ours, scrupulous physical examination including digital rectal examination is key to early diagnosis.